2018
DOI: 10.32553/ijmbs.v2i4.27
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Functional Outcome After Bosworth Technique for Neglected Achilles Tendon Rupture - A Clinical Study

Abstract: Background: Most ruptures of the Achilles tendon occur at the watershed area which is about 2 to 6 cm proximal to insertion of the tendon. There are many techniques of repair like using tendon transfer, autograft or synthetic ligament. Bosworth has described a technique of sural triceps aponeurosis turndown. The study was conducted with the objective to describe the effectiveness and functional outcome after Bosworth procedure in chronic ruptures in zone II in cases where end-to-end repair can’t be done. Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…25 Our study utilized the Bosworth's technique for repair of neglected Achilles tendon tear in zone II and achieved good functional outcomes as 4/5 had excellent results and 1 patient had good functional outcome. Results are in cohesion with studies conducted by Ahmed et al, 18 Agarwal et al 26 No dreaded postoperative complication were seen in our study although a number of studies have reported variable rates of infection, wound dehiscence. 27 Ascertaining the exact size of the graft to restore the length of tendon can be tricky using the Bosworth's technique.…”
Section: Discussionsupporting
confidence: 92%
“…25 Our study utilized the Bosworth's technique for repair of neglected Achilles tendon tear in zone II and achieved good functional outcomes as 4/5 had excellent results and 1 patient had good functional outcome. Results are in cohesion with studies conducted by Ahmed et al, 18 Agarwal et al 26 No dreaded postoperative complication were seen in our study although a number of studies have reported variable rates of infection, wound dehiscence. 27 Ascertaining the exact size of the graft to restore the length of tendon can be tricky using the Bosworth's technique.…”
Section: Discussionsupporting
confidence: 92%